2008
DOI: 10.1143/jjap.47.550
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Temperature Sensitive Li–Zn–Cu Ferrite

Abstract: The authors have fabricated the polycrystalline Li-Zn-Cu ferrite as a new temperature sensitive ferrite. The Li-Zn-Cu ferrite had high-frequency permeability profile and high electrical resistivity as well as the Ni-Zn-Cu ferrite for multilayered surface-mounting device such as a high-frequency chip inductor and filter. Since the new Li-Zn-Cu ferrite had both excellent high-frequency magnetic property and temperature sensitivity, it will be suitable for miniaturization of high-frequency inductive temperature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This ferrite possess unique magnetic, magneto‐optical, magneto‐resistive, thermal, electric, and mechanical properties such as ferromagnetism, excellent creep and radiation damage resistance, high thermal conductivity, high electrical resistivity, controllable saturation magnetization, moderate thermal expansion coefficients, energy‐transfer efficiency, and narrow line width in ferromagnetic resonance [19–21]. These properties make zinc ferrites suitable for numerous device applications, including magnetic materials (circulators, oscillators, and phase shifters for microwave region), sensors, magneto‐optic sensors, anode materials for batteries, catalysts, and sensors for space applications, lasers, phosphorescent sources, microwave and electrochemical devices, and black and brown pigments [22–24]. However, the ferrite in ceramic form has inherent drawback because it is not moldable or flexible to form complex shapes of products.…”
Section: Introductionmentioning
confidence: 99%
“…This ferrite possess unique magnetic, magneto‐optical, magneto‐resistive, thermal, electric, and mechanical properties such as ferromagnetism, excellent creep and radiation damage resistance, high thermal conductivity, high electrical resistivity, controllable saturation magnetization, moderate thermal expansion coefficients, energy‐transfer efficiency, and narrow line width in ferromagnetic resonance [19–21]. These properties make zinc ferrites suitable for numerous device applications, including magnetic materials (circulators, oscillators, and phase shifters for microwave region), sensors, magneto‐optic sensors, anode materials for batteries, catalysts, and sensors for space applications, lasers, phosphorescent sources, microwave and electrochemical devices, and black and brown pigments [22–24]. However, the ferrite in ceramic form has inherent drawback because it is not moldable or flexible to form complex shapes of products.…”
Section: Introductionmentioning
confidence: 99%
“…The oxide phase of Iron-containing transition metal has been the subject of extensive investigations. These oxides posses unique magnetic, magneto-optical, magneto resistive, thermal, electric and mechanical properties such as ferromagnetism, excellent creep and radiation damage resistance, high thermal conductivity, high electrical resistivity, controllable saturation magnetization, moderate thermal expansion coefficients, energy-transfer efficiency, narrow line width in ferromagnetic resonance and others [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It was considered that the magnetic loss m 00 of ferrite enhanced the distributed resistance. Since m 00 was already started rising at 10-100 MHz region, the natural resonance frequency of the ferrite should be made higher from the l/4 resonance frequency by a modification of the ferrite composition or microstructure [5]. The ignored dielectric loss of ferrite may influence Q because it is larger than that of polymer capacitor.…”
Section: Article In Pressmentioning
confidence: 99%
“…Recently, the authors investigated the temperature dependence of magnetic properties of Li-Zn-Cu ferrite [5], and found that its complex permeability exhibits remarkable temperature dependence in a wide temperature range from À35 to 125 1C. It was considered that Li-Zn-Cu ferrite has large temperature coefficient of magnetic anisotropy because this ferrite has no Fe 2+ and high Curie temperature over 400 1C [5]. Furthermore, its temperature dependence of permeability corresponds to simple exponential function.…”
Section: Introductionmentioning
confidence: 99%